Optimization and assessment of quantitative 124I imaging on a Philips Gemini dual GS PET/CT system. - Gregory, R; Hooker, C; Partridge, M; Flux, G (2009)
PURPOSE: Quantitative (124)I PET imaging is challenging as (124)I has a complex decay scheme. In this study the performance of a Philips Gemini dual GS PET/CT system was optimized and assessed for (124)I. METHODS: The energy window giving the maximum noise equivalent count rate (NECR) and NEMA 2001-NU2 image quality were measured. The activity concentration (AC) accuracy of images calibrated using factors from (18)F and (124)I decaying source measurements were investigated. RESULTS: The energy window 455-588 keV gave the maximum NECR of 9.67 kcps for 233 MBq. (124)I and (18)F image quality was comparable, although (124)I background variability was increased. The average underestimation in AC in (124)I images was 17.9 +/- 2.9% for nonuniform background and 14.7 +/- 2.9% for single scatter simulation (SSS) subtraction scatter correction. At 224 MBq the underestimation was 10.8 +/- 11.3%, which is comparable to 7.7 +/- 5.3% for (18)F, but increased with decreasing activity. CONCLUSIONS: The best (124)I PET quantitative accuracy was achieved for the optimized energy window, using SSS scatter correction and calibration factors from decaying (124)I source measurements. The quantitative accuracy for (124)I was comparable to that for (18)F at high activities of 224 MBq but diminishing with decreasing activity. Specific corrections for prompt gamma-photons may further improve the quantitative accuracy.